Rancang Bangun Aplikasi Monitoring Performance WiFi.Id PT.Telekomunikasi Berbasis Web - Ayu Maulisa Lindra; Suroso Suroso; Jon Endri (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Internet is the nessecity that widely used today. One of the way to access the internet it self, we can use the facilities provides by PT.Telekomunikasi that is WiFi.Id. in this application, namely “The WiFi.Id Performance Monitoring Application” can be used to improving the WiFi.Id performance for making it always in good condition and stable. This application is made in web base application where is can be useful for checking WiFi.Id performance that distributed in several point in the fields, the preference from this application we can check in one point from several acceess point without needed to check every point with the provision we still getting a signal that emitted by WiFi.Id access point it self. From this application we can check the quality of bandwidth in every access point, we will know speeds of upload and download that giving and also know the value of ping and jitter in every access point that emitte the signal. This application also can show some of active access point in that location.